STUDENTS' PERCEPTION IN USING PODCAST AS A MEDIUM TO IMPROVE LISTENING SKILL - Nur Syachruni Ramadhani; Nurdin Noni; Muh. Tahir (Universitas Negeri Makassar, 2022)
This research was quantitative approach that aimed to find out the student perception in using podcast as a medium to improve listening skill at English Education study program, Faculty of Language and Literature, State University of Makassar. The research sampel is students English Education 2017, Faculty of Language and Literature, State University of Makassar. Purposive sampling will be used in this research. The data was collected by used Questionnaire and Interview. The result of the data analysis showed that the student and teacher agreed about their easier understanding to the subject when the teacher used podcast in teaching listening. They also agreed that using podcast can help them in remembering the subject. It was proved from the result of the questionnaire and interview. The result of the questionnaire showed that 64% of student stated that the use of podcast in listening helps them in understanding vocabulary in listening to understand the content, and the result of interview showed that podcasting can be a facilitating tool in EFL teaching that helps students mostly in listening. So, it can be concluded that students’ perception on using podcast in teaching listening was positive. By using podcast, they felt more interesting in learning the subject of listening and they didn’t get bored during the lesson, so they can more enjoy understanding the content of listening.